A very low-carbohydrate diabetes prevention program for veterans with prediabetes: a single-arm mixed methods pilot study - Griauzde, Dina H.; Hershey, Cheryl; Michaels, Jamie; Evans, Richard R.; Richardson, Caroline R.; Heisler, Michele; Kullgren, Jeffrey T.; Saslow, Laura R. (Frontiers in Nutrition, 2023)
Introduction: All Veterans Affairs (VA) Medical Centers offer the MOVE! Weight Management Program to help patients achieve and maintain a healthy weight through a calorie-restricted, low-fat diet and increased physical activity. Yet, most MOVE! participants do not achieve clinically significant weight loss of ≥ 5%. A carbohydrate-restricted diet may help more Veterans to achieve ≥ 5% weight loss. Methods: This was a single-arm explanatory sequential mixed methods pilot study conducted in one VA health care system. Veterans with prediabetes and body mass index ≥ 25 kg/m2 were invited to participate in a group-based, virtual, very low-carbohydrate Diabetes Prevention Program (VLC-DPP) consisting of 23 sessions over 12 months. Participants were taught to follow a very low-carbohydrate eating pattern, defined as 20-35 grams of net carbohydrates per day. The primary outcomes were measures of feasibility and acceptability, including program uptake and session attendance. Secondary outcomes included change in weight, hemoglobin A1c, lipids, and patient-reported measures of food cravings, stress eating, perceived health status, and motivation. Interviews were conducted at 6 months to identify factors that facilitated or hindered participants’ achievement of ≥ 5% weight loss. Results: Among 108 screened Veterans, 21 enrolled in the study (19%), and 18 were included in the analytic cohort. On average, participants attended 12.4/16 weekly sessions and 3.6/8 bimonthly or monthly sessions. At 12 months, mean percent weight loss was 9.4% (SD=10.7) with 9 participants (50%) achieving ≥ 5% weight loss. Three factors facilitated achievement of ≥ 5% weight loss among 10/16 interviewees: (1) enjoyment of low-carbohydrate foods; (2) careful monitoring of carbohydrate intake; and (3) reduced hunger and food cravings. Three factors hindered achievement of ≥ 5% weight loss among 6/16 interviewees: (1) food cravings, particularly for sweets; (2) challenges with maintaining a food log; and (3) difficulty with meal planning. Conclusions: A VLC-DPP is feasible and acceptable and shows preliminary efficacy among Veterans with prediabetes. The program’s weight loss effectiveness compared to standard MOVE! should be evaluated in a larger-scale trial. Such a program may be offered in addition to the standard MOVE! program to expand the menu of evidence-based lifestyle counseling options for Veterans.